Activated Clotting Time and Outcomes During Percutaneous Coronary Intervention for Non–ST-Segment–Elevation Myocardial Infarction. (April 2015) - Ducrocq, Gregory; Jolly, Sanjit; Mehta, Shamir R.; Rao, Sunil V.; Patel, Tejas; Moreno, Raul; Gao, Peggy; Steg, Philippe Gabriel
<x xml:space="preserve">Abstract</x> Background— Activated clotting time (ACT) is widely used to guide unfractionated heparin dosing during percutaneous coronary intervention. However, its value in predicting complications is controversial in the modern era. We sought to examine the relationship between ACT and outcomes in non–ST-segment–elevation acute coronary syndrome patients. Methods and Results— In the Fondaparinux With Unfractionated Heparin During Revascularization in Acute Coronary Syndromes (FUTURA/OASIS-8) trial, 2026 patients with non–ST-segment–elevation acute coronary syndrome treated with fondaparinux 2.5 mg/d and undergoing percutaneous coronary intervention were randomized to low-dose unfractionated heparin (50 U/kg) or standard-dose unfractionated heparin (85 U/kg or 60 U/kg with glycoprotein IIb/IIIa inhibitors, with ACT guidance). No difference was shown for major bleeding and there was a trend toward a reduction in ischemic events with standard-dose unfractionated heparin. To clarify the additional value of ACT guidance, we analyzed with logistic modeling peri–percutaneous coronary intervention outcomes according to peak ACT as a linear function. A threshold effect was then investigated. No linear correlation was found between ACT and thrombotic or bleeding events. In patients not receiving planned glycoprotein IIb/IIIa inhibitors, a significant increase in rates of death, myocardial infarction, and target vessel revascularization was identified in patients with an ACT⩽300 s (4.86% versus 2.78%; adjusted odds ratio, 1.84; 95% confidence interval, 1.06–3.21; P=0.03). No threshold was found for hemorrhagic complications in patients with or without glycoprotein IIb/IIIa inhibitors. Conclusions— Non–ST-segment–elevation acute coronary syndrome patients undergoing percutaneous coronary intervention with an ACT⩽300 s are at increased risk of thrombotic complications. ACT, however, does not predict hemorrhagic complications. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00790907.